Is Fecal Calprotectin an Applicable Biomarker of Gut Immune System Activation in Chronic Inflammatory Demyelinating Polyneuropathy? – A Pilot Study - Koszewicz, Magdalena; Mulak, Agata; Dziadkowiak, Edyta; Budrewicz, Sławomir (Frontiers in Human Neuroscience, 2021)
Introduction: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a complex autoimmune disease caused by dysregulated response to not fully recognized antigens. Some association between CIDP and inflammatory bowel disease (IBD) has been reported, but the exact pathophysiological links of these disorders are not well understood. Aim of the Study: To evaluate fecal calprotectin as a biomarker of gut inflammation in CIDP patients without IBD. Methods: Fifteen patients with CIDP and 15 healthy controls were included in the study. The CIDP diagnosis was based on the EFNS/PNS criteria. The occurrence of bowel symptoms was assessed based on a questionnaire. The quantitative evaluation of fecal calprotectin level was performed by the ELISA test. Results: The fecal calprotectin level (μg/g) expressed as median along with the lower and upper quartiles [25Q–75Q] was significantly higher in CIDP patients compared to the controls: 26.6 [17.5–109.0] vs 15.6 [7.1–24.1], p = 0.0066. Abnormal fecal calprotectin level (>50 μg/g) was found in 33% of all CIDP patients and in none of the control subjects. The patients with abnormal fecal calprotectin level did not differ from the rest of the study group regarding the neurological status. The most common bowel symptoms reported by CIDP patients included constipation (33%), feeling of incomplete evacuation (33%), bloating (27%), and alternating bowel movement pattern (27%). Conclusion: In one-third of CIDP patients the signs of gut immune system activation have been observed. This finding may be associated with CIDP pathogenesis and induction of autoimmune response as well as concomitant dysautonomia with gastrointestinal symptoms.